Timing Matters: Analyzing Government Intervention Intensity and Effectiveness in Controlling Rumor Spread - Yuxun Zhou; Mohammad Mafizur Rahman; Ren Long; Xiaoyun Liu (IEEE Access)
This study aims to research how government intervention intensity and effectiveness can control rumor spread under the condition of distinguishing the timing of intervention. This study establishes two extended Susceptible-Exposed-Infected-Removed (SEIR) models and then uses numerical analysis to simulate the impact of government intervention intensity and intervention effectiveness on rumor spread under different situations. There are two main findings in this research: 1. Government intervention, in terms of both intensity and effectiveness, significantly reduces the spread and impact of rumors. Higher intervention levels not only diminish the rumor’s reach but also slow down its spread. 2. The timing of intervention strategies should vary based on specific conditions: Pre-exposure interventions are recommended when intervention intensity is low, when intensity is high but the rumor is expected to last long, or when both intensity and effectiveness are high with a short rumor duration. Post-exposure interventions are more effective when both intensity and effectiveness are high, and the rumor spread is expected to last long. This study has two theoretical innovations: 1. It extends the traditional rumor propagation model by adding a government intervention component. 2. It introduces the concept of intervention timing, distinguishing between pre-exposure and post-exposure phases, thus enhancing the understanding of how timing affects rumor control. These insights can inform strategies for monitoring and managing public opinion across various fields.